Statement of Peer Review - Julio A. Seijas (Chemistry Proceedings)
In submitting conference proceedings to Chemistry Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]